Willingness of Graduate Nursing Students to Provide Care for COVID-19 Patients - Andrea Beatrice Josef; Hannah Grace Pascual; Antonette Mei Surigao; Jemina Fuentebella; Kathyrine Calong Calong; Gil P. Soriano; Carissa Juliana Balaria; Ryan Michael F. Oducado (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
Nurses play a key role in management and care services to maintain patient safety; however, with the emergence of COVID-19, the number of nurses still continues to decline. Due to the on-going problem that even novice nurses may see as a major challenge, this study aims to identify whether nursing graduates are willing to participate in the care of COVID-19 patients. The study is cross-sectional where a total of 146 conveniently chosen nursing graduates currently enrolled in Nursing Review Centers in the Philippines preparing to take the Nurse Licensure Examination. The data were collected using Google forms from August to September 2020 using a four-part questionnaire which includes demographic information sheet, COVID-19 Perceived Risk Scale, Fear of COVID-19 Scale, and questions pertaining to their willingness to care for COVID-19 patients. Descriptive statistics such as frequency, percentage, mean, and standard deviation and inferential statistics such as Mann-Whitney U test, Kruskal-Wallis and Spearman rho were used to analyze the data. After gathering the information from the participants, the results had ultimately shown that the majority of the participants (86.3%) are willing to care for COVID-19 patients. The ones with the most significant positive correlation with willingness were age (p = 0.008), self-reported health (p = 0.000), self-reported knowledge about COVID-19 (p = 0.001), and interest to become a Registered Nurses (p = 0.000). Based on these results, the majority of the participants had been willing to care for patients with COVID-19, although the factors that influence were associated with their willingness differ. Keywords: COVID-19, nursing graduates, willingness Abstrak Kesediaan Lulusan Mahasiswa Keperawatan dalam Memberikan Perawatan Pasien COVID-19. Perawat memainkan peran kunci dalam manajemen dan pelayanan perawatan untuk menjaga keselamatan pasien; namun dengan munculnya COVID-19 jumlah perawat semakin berkurang. Masalah ini masih berlangsung dan dianggap sebagai tantangan besar bahkan oleh perawat pemula, oleh karena itu penelitian ini bertujuan untuk mengidentifikasi apakah lulusan keperawatan bersedia berpartisipasi dalam perawatan pasien COVID-19. Studi ini menggunakan metode cross-sectional dan dilakukan pada 146 lulusan keperawatan yang terdaftar di Pusat Tinjauan Keperawatan (Nursing Review Centers) di Filipina dan sedang bersiap untuk mengikuti ujian lisensi perawat (Nurse Licensure Examination). Data dikumpulkan menggunakan formulir Google dari Agustus hingga September 2020 menggunakan kuesioner empat bagian yang meliputi lembar informasi demografi, Skala Persepsi Risiko COVID-19, Skala Ketakutan terhadap COVID-19, dan pertanyaan terkait kesediaan mereka untuk peduli terhadap pasien COVID-19. Statistik deskriptif seperti frekuensi, persentase, mean, dan standar deviasi serta statistik inferensial seperti Mann-Whitney U test, Kruskal-Wallis, dan Spearman rho digunakan untuk menganalisis data. Setelah mengumpulkan informasi dari para peserta, hasilnya menunjukkan bahwa mayoritas peserta (86,3%) bersedia merawat pasien COVID-19. Korelasi positif yang paling signifikan dengan kemauan adalah usia (p = 0,008), laporan kesehatan diri (p = 0,000), pengetahuan yang dilaporkan sendiri tentang COVID-19 (p = 0,001), dan minat menjadi registered nurse (p = 0,000). Berdasarkan hasil tersebut, mayoritas peserta telah bersedia merawat pasien COVID-19, meskipun faktor yang memengaruhi kesediaannya berbeda-beda. Kata Kunci: COVID-19, kesediaan, lulusan keperawatan